2012 IEEE International Symposium on Information Theory Proceedings 2012
DOI: 10.1109/isit.2012.6283511
|View full text |Cite
|
Sign up to set email alerts
|

List-decoding of subspace codes and rank-metric codes up to Singleton bound

Abstract: Subspace codes and rank-metric codes can be used to correct errors and erasures in network, with linear network coding. Both types of codes have been extensively studied in the past five years.Subspace codes were introduced by Koetter and Kschischang to correct errors and erasures in networks where topology is unknown (the non-coherent case). In this model, the codewords are vector subspaces of a fixed ambient space; thus codes for this model are collections of such subspaces. In a previous work, we have devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 21 publications
1
52
0
Order By: Relevance
“…This implies that decoding radius of list decoding the square Gabidulin codes is not better than unique decoding. Inspired by good list decodability of the folded Reed-Solomon codes [12], people started to consider list decoding of folded Gabidulin codes [19]. However, the rate of the folded Gabidulin code in [19] tends to 0.…”
Section: Known Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that decoding radius of list decoding the square Gabidulin codes is not better than unique decoding. Inspired by good list decodability of the folded Reed-Solomon codes [12], people started to consider list decoding of folded Gabidulin codes [19]. However, the rate of the folded Gabidulin code in [19] tends to 0.…”
Section: Known Resultsmentioning
confidence: 99%
“…Inspired by good list decodability of the folded Reed-Solomon codes [12], people started to consider list decoding of folded Gabidulin codes [19]. However, the rate of the folded Gabidulin code in [19] tends to 0. In 2013, Guruswami and Xing [17] considered subcodes of the Gabidulin codes via point evaluation in a subfield and showed that list decodability of subcodes of the Gabidulin codes achieves the Singleton bound τ = 1 − R. However, the ratio ρ = n/t of the rank-metric code C ⊆ M n×t (F q ) constructed by Guruswami and Xing [17] is Θ(ε 2 ).…”
Section: Known Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mahdavifar-Vardy (MV) codes [25,27] are subspace codes constructed by evaluating powers of skew polynomials at certain points. We will describe how one can use row reduction to carry out the most computationally intensive step of the MV decoding algorithm given in [27], the Interpolation step.…”
Section: Decoding Mahdavifar-vardy Codesmentioning
confidence: 99%
“…[6]; to the best of our knowledge, analogous generalisations over skew polynomial rings have yet to see any applications.Lately, there has been an interest in Gabidulin codes over number fields, with applications to space-time codes and low-rank matrix recovery [3]. Their decoding can also be reduced to a shift-register type problem [29], which could be solved using the algorithms in this paper (though again, one should analyse the bit-complexity).Mahdavifar-Vardy (MV) codes [25,27] are subspace codes whose main interest lie in their property of being list-decodable beyond half the minimum distance. Their rate unfortunately tend to zero for increasing code lengths.…”
mentioning
confidence: 99%